2020
DOI: 10.1016/j.chempr.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Size-Selective Catalytic Polymer Acylation with a Molecular Tetrahedron

Abstract: We report an original catalytic molecular tetrahedron. By threading through the cavity of the tetrahedron, polymeric substrates are unfolded or broken apart. Our catalyst distinguishes between polymer chains of different lengths, functionalizing the shorter polymers selectively over the longer ones-as a proof of concept for selective catalysis to modify polymers. Our findings advance the fundamental understanding of the thermodynamic and kinetic phenomena controlling the interactions between molecular cages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 65 publications
7
30
1
Order By: Relevance
“…13,63,64 Remarkably, even polymers can be modified in a site-selective manner following this approach. 65 Regio-selectivity can be modulated in a similar way. As an example, Ribas and coworkers recently applied this approach to accomplish a highly regio-selective poly-functionalization of fullerene (Fig.…”
Section: A Supramolecular Shadow Mask To Control Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…13,63,64 Remarkably, even polymers can be modified in a site-selective manner following this approach. 65 Regio-selectivity can be modulated in a similar way. As an example, Ribas and coworkers recently applied this approach to accomplish a highly regio-selective poly-functionalization of fullerene (Fig.…”
Section: A Supramolecular Shadow Mask To Control Selectivitymentioning
confidence: 99%
“…171 Other outstanding examples of processive catalysts have been reported by Harada, 172 who coupled α-and β-cyclodextrins to polymerize δ-valerolactone, by Leigh who prepared a pseudo-rotaxane in which, during its oriented dethread along the axis, the wheel iteratively and sequentially acquires three aminoacids 173 (or four in a more recent development 174 ) to form a pendant peptidic chain, and lately by Li and Schneebeli who obtained the size-selective acylation of the amino groups present in the chains of polydisperse polymer mixtures by threading the polymer chains into hydrazone-based molecular tetrahedrons decorated with tryglime units. 65…”
Section: Processive Catalysismentioning
confidence: 99%
“…Particularly attractive design goals are molecular scaffolds for catalysis as potentially more general and versatile alternatives to biological enzymes. As with enzymes, both steric features and electric fields are important considerations for the catalytically active site(s) (cf.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Self-assembled metal-organic cages are useful for a range of applications including catalysis, biomedicine, molecular sensing, gas absorption and molecular separation. [21][22][23][24][25] Previous studies have shown that various metal organic assemblies can recognize the structure of DNA G4 and alter its conformation. [5][6][7][26][27][28][29][30] The structural tunability and encapsulation ability of coordination cages render them useful for biosensing, drug delivery and cancer therapy.…”
Section: Introductionmentioning
confidence: 99%